Predicting physical stability of pharmaceuticals and investigating use of Raman spectroscopy to interrogate molecular relaxation events - Lee, Para (2023)
Poor water solubility and slow dissolution are common issues in pharmaceuticals. The pharmaceutical industry widely employs amorphous solid dispersion to enhance dissolution, accelerate it, and promote bioavailability.